Frações contínuas - um estudo sobre "boas" aproximações - Bezerra, Rafael Tavares Silva (2016)
The study of ontinued fra tions will start with some histori al fa ts, aiming at a better understanding of the subje t. We will bring the de nition of ontinued fra tions for a number α real, with the de nition for α rational and α irrational. The dis ussion will fo us on meaning results for the al ulation of redu ed and good approximations of irrational numbers, also aimed at determining the error between the redu ed and the irrational number. We will bring a study of the periodi ontinued fra tions, with emphasis on Lagrange theorem, whi h relates a periodi ontinued fra tion and a quadrati equation. Finishing with a fo us on problem solving, as the al ulation of ontinued fra tions of irrational numbers of the form √a2 + b, as well as proof of the irrationality of e by al ulating its ontinued.